2022
DOI: 10.3389/fmicb.2022.1041425
|View full text |Cite
|
Sign up to set email alerts
|

Taxogenomic status of phylogenetically distant Frankia clusters warrants their elevation to the rank of genus: A description of Protofrankia gen. nov., Parafrankia gen. nov., and Pseudofrankia gen. nov. as three novel genera within the family Frankiaceae

Abstract: The genus Frankia is at present the sole genus in the family Frankiaceae and encompasses filamentous, sporangia-forming actinomycetes principally isolated from root nodules of taxonomically disparate dicotyledonous hosts named actinorhizal plants. Multiple independent phylogenetic analyses agree with the division of the genus Frankia into four well-supported clusters. Within these clusters, Frankia strains are well defined based on host infectivity range, mode of infection, morphology, and their behaviour in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…In addition, we also analyzed the differences in the abundance of all 19 Frankia species contained in RN at different sites ( Supplementary Table S8 ). These 19 Frankia species were distributed in different Frankia clusters ( Hong et al., 2012 ; Nouioui et al., 2019 ; Gtari, 2022 ). We observed that most of the Frankia species in the RN microbial community did not differ significantly between the different sites, but their relative abundance was very low.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we also analyzed the differences in the abundance of all 19 Frankia species contained in RN at different sites ( Supplementary Table S8 ). These 19 Frankia species were distributed in different Frankia clusters ( Hong et al., 2012 ; Nouioui et al., 2019 ; Gtari, 2022 ). We observed that most of the Frankia species in the RN microbial community did not differ significantly between the different sites, but their relative abundance was very low.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome of the whole-genome sequence analysis provides further evidence that much better resolution is found between actinomycetes in phylogenomic trees than in corresponding 16S rRNA gene and MLSA trees as the former are based on millions not hundreds of unit characters [4,5]. It is evident from the phylogenomic tree (Fig.…”
Section: Whole-genome Sequencing and Genomic Analysesmentioning
confidence: 97%
“…The outcome of the whole-genome sequence analysis provides further evidence that much better resolution is found between actinomycetes in phylogenomic trees than in corresponding 16S rRNA gene and MLSA trees as the former are based on millions not hundreds of unit characters [4, 5]. It is evident from the phylogenomic tree () that the isolates form a distinct lineage within a clade that includes the type strains of Streptantibioticus cattleyicolor , Streptomyces ferralitis , S. parmotrematis and S.…”
Section: Whole-genome Sequencing and Genomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parafrankia is a bacterial genus classified within the Frankiaceae family, alongside the genera Frankia, Protofrankia, and Pseudofrankia 1 , 2 . Parafrankia strains are known for their ability to form symbiotic relationships with actinorhizal plants of the Elaeagnaceae , Colletieae ( Rhamnaceae ), Morella ( Myricaceae ), and Gynmnostoma ( Casuarinaceae ) species.…”
Section: Introductionmentioning
confidence: 99%